Acteurs et stratégie de gouvernance dans le contexte du régionalisme politique au Maniema de 2007 à 2015 - Morisho, Adolphe Ndokili (IJRDO - Journal of Business Management, 2021)
The Democratic Republic of Congo, like other African countries, committed since more of one decade, in a set of the reforms aiming to straighten the socioeconomic situation, to rationalize and to modernize his/her/its governance. This reform enroll in the time and rest on an institutional diagnosis, which reveals dysfunctions of the state-controlled device due to the maladjustment of governance system to the socio-cultural contexts. It is in this perspective that we entered into this reflection, in order to identify the actors and their interactions and to examine their strategy of the governance in the context of the political regionalism in the Maniama, for one active period of 2007 to 2015. To the analysis, he/it was revealed that the strategy adopted by the actors of the governance was deficient to the look of the stake for which they are all mobilized and committed. It is the emergence of the province or better his/her/its development that definitely should pass by the reduction of poverty and the economic growth.